BS61 PKCαα knock-down enhances intimal calcification in a murine model of atherosclerosis. (May 2019) - Borland, Samantha; Behnsen, Julia; Akerele, Abimbola; Sherratt, Michael J; Brennan, Keith; Holt, Cathy; Francis, Sheila; Canfield, Ann
Abstract : Intimal calcification is the formation of mineralised tissue within atherosclerotic lesions and can lead to an increased risk of plaque rupture and mortality in man. Even though experimental data are sparse, it had been suggested that inhibiting protein kinase Cα (PKCα) may be of therapeutic benefit in atherosclerosis. However, we recently discovered that loss of PKCα increases mineral deposition by vascular smooth muscle cells (VSMCs) in a transforming growth factor-β (TGFβ)-dependent manner in vitro, suggesting that vascular calcification and its devastating consequences could be increased if patients with cardiovascular disease are treated with PKCα inhibitors. This study tests the hypothesis that PKCα regulates atherosclerosis and intimal calcification in vivo. Nine to ten week-old male PKCα knock-out (PKCα-/-) mice crossed with ApoE-/- mice (PKCα-/-ApoE-/-) were fed a high-fat, high-cholesterol diet (Western diet) for 8, 18 and 28 weeks. Male ApoE-/- mice fed the same diet were used as controls. En face Oil Red O staining was significantly increased (∼1.5-fold, P<0.05) in the aortae of PKCα-/-ApoE-/- mice after 18 weeks of Western diet feeding when compared to ApoE-/- controls. This difference in lesion size is greatest in the athero-resistant descending aorta when compared to the athero-prone aortic arch, suggesting PKCα plays a protective role in atherosclerosis; particularly in athero-resistant vascular beds. Aortic sinus lesion size was not significantly different between PKCα-/-ApoE-/- and ApoE-/- mice at any time point. However, a significant increase in intimal calcification (∼2-fold, P<0.05) accompanied by a decrease in aortic sinus cholesterol cleft/necrotic core area (∼1.5-fold, P<0.05) was observed at the 28 week time-point in PKCα-/-ApoE-/- mice versus ApoE-/- controls. Thus, loss of PKCα increases aortic sinus calcification in the absence of any effect on lesion size in ApoE-/- mice. To further characterise the calcifications in PKCα-/-ApoE-/- and ApoE-/- mice, detailed morphometric analysis of whole brachiocephalic arteries was performed using microCT. Large calcified structures (ranging from 50–850μm) containing pores (ranging from 8–35μm) were localised within lesions in the brachiocephalic artery of PKCα-/-ApoE-/- and ApoE-/- mice. These calcifications were localised solely to lesions at the base of the brachiocephalic artery in ApoE-/- mice whereas in PKCα-/-ApoE-/- mice, additional calcifications were observed at the bifurcation. In conclusion, our study has identified that PKCα may play a protective role in both atherosclerosis and intimal calcification. This suggests that inhibiting PKCα may not be of any therapeutic benefit in atherosclerosis. Activation of PKCα could instead represent a new therapeutic target for atherosclerosis-induced intimal calcification. Conflict of interest: None